2011
DOI: 10.1007/s11695-011-0578-8
|View full text |Cite
|
Sign up to set email alerts
|

Obese Women’s Perception of Bariatric Trans-vaginal NOTES

Abstract: Much of the discussion pertaining to natural orifice transluminal endoscopic surgery (NOTES) focuses on technical issues, with little attention to women's perception and to their willingness to consent to this surgery, especially in the field of obesity. Aim of this study was to evaluate obese women's perception of NOTES and trans-vaginal access. Sixty two obese patients undergoing bariatric surgery were given a written description of NOTES with an anonymous questionnaire exploring their concerns and opinions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…20 Overall, 62 patients (mean body mass index 45.3 kg/m 2 ) entered the study. The risk of complications was classified as the most important factor by 87.1% of patients.…”
Section: Comment Which Patients Would Prefer Notes and Why?mentioning
confidence: 99%
See 1 more Smart Citation
“…20 Overall, 62 patients (mean body mass index 45.3 kg/m 2 ) entered the study. The risk of complications was classified as the most important factor by 87.1% of patients.…”
Section: Comment Which Patients Would Prefer Notes and Why?mentioning
confidence: 99%
“…16 In the study by Rocchietto et al, 83.9% of patients stated that they were concerned about the postoperative infection rate related to NOTES. 20 Among younger patients, all reported concerns about NOTES' effects on their sexual activity and the potential risk of dyspareunia. Moreover, the influence of NOTES on future fertility was considered very important for 85.7% of the nulliparous women who were surveyed.…”
Section: What Are Patients' Explicit Concerns About Notes?mentioning
confidence: 99%
“…In the five studies which also asked about preference of NOTES access routes, four reported an overwhelming preference for transoral or transgastric access [18,22,23,26], whereas transrectal access was the preferred route in the study by Hucl et al [27]. All studies which included the option of transvaginal access reported this to be the least preferred option.…”
Section: Preference For Notesmentioning
confidence: 99%
“…When asked to compare to laparoscopy, preference rates for NOTES ranged from 26 [22] to 78 % [23] in seven studies. Across all studies, 48 % (1,163/2,405) patients indicated a preference for NOTES.…”
Section: Preference For Notesmentioning
confidence: 99%
See 1 more Smart Citation